A LONG JOURNEY TO EUROPE: THE PERCEPTION OF THE EUROPEAN UNION DURING THE IMPLEMENTATION OF THE PROJECT “JADAR” AND STUDENT PROTESTS IN SERBIA - Klačar, Bojan (Political Review, 2025)
This paper researches the public perception of the European Union (EU) and the process of European integration in Serbia amid the context of large-scale student protests that began in November 2024 and the major tragedy in Novi Sad, as well as the ongoing lithium crisis associated with the controversial “Jadar” project. The aim of the study is to explore how the project “Jadar” and the student protests have affected the EU’s reputation and position within Serbian public opinion, to identify the social groups in which attitudes toward the EU are deteriorating, and to assess the potential long-term implications for the European integration process. The theoretical and methodological framework is grounded in literature emphasizing stability as a central point in the recent past of the EU’s approach to the Western Balkans – often at the expense of democratic principles – and incorporates data from a quantitative public opinion poll conducted on a nationally representative sample. Findings indicate that both the student protests and the lithium mining controversy have adversely influenced public attitudes toward the EU. Notably, this decline in support is observed even among pro-EU citizens, particularly in response to the EU’s official stance on the protests. Public opinion remains highly sceptical regarding the perceived (economic or developmental) benefits of the “Jadar” project, with environmental concerns and doubts over compliance with ecological standards prevailing. Moreover, a considerable portion of citizens critical of the EU’s role in the lithium mining process are individuals who already oppose Serbia’s EU accession. Regarding the student protests, the majority of the public expresses dissatisfaction with the EU's reactions – some perceiving them as too mild, while others regard them as excessively explicit and critical.
Keywords: public opinion poll; European Union; students; lithium; European integration; EU membership